2017
DOI: 10.1007/s11998-016-9905-2
|View full text |Cite
|
Sign up to set email alerts
|

Acid-resistant organic coatings for the chemical industry: a review

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…Detailed explanations and studies into physical and chemical degradation of organic coatings are covered in [2].…”
Section: Degradation Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed explanations and studies into physical and chemical degradation of organic coatings are covered in [2].…”
Section: Degradation Mechanismsmentioning
confidence: 99%
“…The added stress of low pH exposure decreases the erosion resistance of all selected coatings by reacting with the resin and/or fillers. In a recent review [2], certain functional groups in cured coating resins were reported as vulnerable to acidic hydrolysis, which would cause chain scissoring in the resin matrix and thus change surface mechanical properties. These groups include amine linkages in NE1, urethane linkages in PU, and ester bonds in VE.…”
Section: Chemical Reaction Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a mature technology, thermal spraying process has been widely used to deposit ceramic coatings on different metals, such as steels [4,5,6], irons [7], aluminium alloys [8], superalloys [9] to protect the substrate from wear [10,11], corrosion [12], thermal fatigue [13] and cavitation erosion [14] for a long service life. Oxide ceramics, due to their excellent properties including high hardness, high chemical inertness [13,14] in a variety of aggressive environments [15], and good wear resistance, are promising candidates as corrosion-resistant coatings in industrial applications, although there are some inevitable defects in the coatings [16,17]. Generally, the defects come from unmelted particles, inadequate flow or fragmentation of molten particles under impact status, shadowing effects caused by an improper spraying angle, and entrapped gas [18].…”
Section: Introductionmentioning
confidence: 99%